Menumbuhkan Budaya Menabung Sejak Dini pada Anak Melalui Program Pembuatan Celengan di Pojok Literasi: Pengabdian kepada Masyarakat di Desa Raksabaya-Ciamis - Tazqia Ainul Qolbi; Andifa Dwi Fani; Asni Nuraeni; Ayi Yulianti Fadila; Alifa Irna Yasin; Rita Rosmiati (Khidmat, 2022)
Recently, the condition of literacy in Indonesia has decreased. This is due to the public's low interest in dealing with everything related to literacy. Based on the 2019 OJK survey, financial literacy in Indonesia is still in the low category at 38.3%. When compared with several other countries, the level of financial literacy in Indonesia is still far behind. The type of research used is participatory action research (PAR) using a qualitative approach. The data in this research is analytical and descriptive; the data was obtained through observation of the research subjects, namely children in Raksabaya village. With this program, all children have an understanding of the importance and the benefit of saving